(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This study examined the relationship between supply chain reliability and export competitiveness of agro-industries in Southern Nigeria. Specifically, the study investigated the influence of information sharing and logistics reliability on the Export Competitiveness Index of selected agro-industrial firms. A quantitative research design employing a descriptive survey approach was adopted. Data were collected from 187 managerial and operational staff across export-oriented agro-industrial firms in the South-South region of Nigeria. The data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis with the aid of SPSS version 26. Findings revealed that information sharing (r = 0.548, p < 0.01; β = 0.298, p < 0.001) and logistics reliability (r = 0.621, p < 0.01; β = 0.441, p < 0.001) both have significant positive effects on export competitiveness. Logistics reliability emerged as the strongest predictor of export competitiveness. The regression model explained 47 percent of the variance in export competitiveness. The study concludes that strengthening supply chain coordination and logistics systems is critical for improving non-oil export performance and enhancing the global competitiveness of agro-industries in Southern Nigeria. The study recommends increased investment in digital information-sharing platforms, resilient logistics infrastructure, and supportive trade facilitation policies.